Proceedings of Workshop on Managing and Mining Enriched Geo-Spatial Data 2014
DOI: 10.1145/2619112.2619115
|View full text |Cite
|
Sign up to set email alerts
|

On the Correlation Between Textual Content and Geospatial Locations in Microblogs

Abstract: Microblogs allow users to publish geo-tagged posts-short textual messages assigned to a geographic location. Users send posts from places they visit and discuss an idiosyncratic mixture of personal and general topics. Thus, it is reasonable to assume that the locations and the textual content of posts will be unique and will identify the posting user, to some extent. This raises the question whether there is a correlation between the locations of posts and their content. Are users who are similar from the geos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Previous research [41,42] has shown the correlation between the content of the tweets and their geographical location. This is because high similar tweets are related to the same topic/event, and therefore they are likely to be posted in the same location.…”
Section: Similarity Score and Tweet Geolocationmentioning
confidence: 99%
“…Previous research [41,42] has shown the correlation between the content of the tweets and their geographical location. This is because high similar tweets are related to the same topic/event, and therefore they are likely to be posted in the same location.…”
Section: Similarity Score and Tweet Geolocationmentioning
confidence: 99%
“…In fact, the data may expose trends that would be non-obvious to a person. For example, the n-gram Nintendo turns out to be location-sensitive in some New York datasets [8], due to the Nintendo store at Rockefeller Plaza.…”
Section: Metricsmentioning
confidence: 99%
“…Indeed, localizing social media items is not an easy task for several reasons [8]. First, it is a priori unknown which areas will be associated with textual terms and which will not.…”
Section: Introductionmentioning
confidence: 99%
“…Note that they find popular terms for given locations while we search for locations for given terms. For a study of the correlation between locations and content in microblogs see [6]. The MapD 2 system and TweetMap 3 (which is built on top of MapD) provide search capabilities over geotagged tweets, however, these systems employ a "brute-force approach" and require a huge computation power while our system can run on an ordinary computer.…”
Section: Related Workmentioning
confidence: 99%